Teacher Perceptions on the Use of the Wordwall.Net Application as an English Vocabulary Learning Media - Galuh Raga Paksi; Rita Karmila Sari; Somawati Somawati (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to determine the teacher's perception of using the Wordwall.net application as a medium for learning English vocabulary. This research is descriptive research with a quantitative approach. The research data was the teacher's perception of using the Wordwall.net application as a medium for learning English vocabulary. The data source is teachers at SDN Makassar 06, East Jakarta. Data was collected using a questionnaire. The data from the questionnaire were then tabulated, analyzed, and interpreted. This study found positive perceptions from teachers towards the use of the Wordwall.net application as a medium for learning English vocabulary. This study concludes that teachers are satisfied with learning media Wordwall.net to use in teaching English vocabulary